Electron Beam Irradiation Elicits Dose-Dependent Physio-Biochemical Responses and Antioxidant Defense Modulation in Sugarcane (Saccharum spp. hybrid) - Hai-Rong Huang; Kai-Chao Wu; Meng-Ling Weng; Krishan K. Verma; Tian Pang; Ling-Ling Liang; Zhi-Nian Deng; Lin Xu (Sugar Tech, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Study on Fertility and Genetic Diversity of Introduced Sugar Beet Germplasm Resource FC220 - Shi-Kun Zhang; Ya-Dan Xiao; Lin Liao; Ze-Dong Wu; Lin-Lin Sun (Sugar Tech, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Collection, Characterization, and Diversity Analysis of New Wild Sugarcane Germplasm from Southeastern Yunnan Province, China - Chaohua Xu; Xuekuan Chen; Fenggang Zan; Peifang Zhao; Wei Qin; Chunyan Tian; Xiuqin Lin; Chunyan Kong; Hongbo Liu; Tanweer Kumar; Faisal Mehdi; Mahmoud H. M. Ebid; et al. (Sugar Tech, 2025)

Genetic Diversity Analysis of 89 Monogerm Maintainer Lines of Sugar Beet - Jing-Jing Zhao; Lin-Lin Sun; Zhi Pi; Sheng-Nan Li; Ze-Dong Wu (Sugar Tech, 2025)

Stability and Adaptability of Sugar Beet Examined Based on AMMI and BLUP–GGE Biplot Analyses - Yuhang Lin; Xinwang Dang; Xiaohang Hu; Yanli Li; Shuo Liu (Sugar Tech, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Determination of Multiple Pesticide Residues and Dietary Intake Risk Assessment of 35 Pesticides in Beet from Five Provinces of Northern China - Zichen Wang; Bingshan Jiang; Caiwei Pang; Lin Liu; Qin Zhou (Sugar Tech, 2025)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Screening of Artificial Diet Formulations for Sugarcane Stalk Borer Chilo sacchariphagus Bojer - Ji-li Wei; Xue-hong Pan; Xian-kun Shang; Cheng-hua Huang; Yong-lin Ma (Sugar Tech, 2023)

Herbicidal Activity Evaluation of Topramezone and Its Safety to Sugarcane - Yong-lin Ma; Cheng-lin Guo; Yan-hui Wang; Yuan-yuan Gao; Jian-lin Qin; Ji-li Wei (Sugar Tech, 2023)

Structure, Intracellular Localisation and Expression Analysis of Sucrose Nonfermenting-Related Kinase ShSnRK1α in Sugarcane - Ting-ting Zhao; Jun-gang Wang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2023)

Optimization Research on the Working Parameters of Sugarcane Harvester on the Cutting Time of Stalks Using Virtual Prototype Technology - Zhi Li; Zhaoli Lin; Shiyan Li; Hua Zhang (Sugar Tech, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Detection of Key Brown Rust Resistance Gene, Bru1, in 200 Sugarcane (Saccharum L.) Ancestral Species and Landraces Using a Four-Primer Molecular Marker - Xujuan Li; Chaohua Xu; Jun Mao; Hongbo Liu; Chunjia Li; Xinlong Liu; Xiuqin Lin; Chunyan Kong; Xin Lu (Sugar Tech, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Comparison of IC-RT-PCR, Dot-ELISA and Indirect-ELISA for the Detection of Sorghum Mosaic Virus in Field-Grown Sugarcane Plants - Hai Chen; Niyaz Ali; Wenzhu Lv; Yanan Shen; Zhen Qing; Yinfu Lin; Baoshan Chen; Ronghui Wen (Sugar Tech, 2020)

Characteristics, Expression Pattern and Intracellular Localisation of Sugarcane Cytoplasmic Hexokinase Gene ShHXK8 - Jun-gang Wang; Ting-ting Zhao; Ben-peng Yang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2019)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Reverse Transcription–Recombinase Polymerase Amplification Assay for the Detection of Sugarcane Streak Mosaic Virus in Sugarcane - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Shu-Zhen Zhang (Sugar Tech, 2019)

Polyphenol Removal from Sugarcane Juice by Using Magnetic Chitosan Composite Microparticles - Xing-quan Liang; Song-lin Fan; Jia-xing Zhang; Xiao-rong Song (Sugar Tech, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Development of a Reverse Transcription-Recombinase Polymerase Amplification Assay for Detection of Sugarcane Yellow Leaf Virus - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

An Assessment of Genetic Diversity of Yield-Related Traits of Saccharum spontaneum from Yunnan Province, China - Chaohua Xu; Huosheng Su; Hongbo Liu; Xin Lu; Xujuan Li; Chunjia Li; Xiuqin Lin; Jun Mao; Qiuyan Zi; XinLong Liu (Sugar Tech, 2017)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Effects of Sugarcane Ratooning Cultivation on the Alteration of Bacterial Communities in the Rhizosphere Soil - Lin Sheng; Zhang Aijia; Wang Rongyu; Cheng Ting; Zhou Mingming; Yuan Zhaonian; Lin Wenxiong (Sugar Tech, 2012)

Combined application of NPK on yield quality of sugarcane applied through SSDI - Lin Xu; Hai-Rong Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2010)

Molecular responses to the fungal pathogen Gibberella fujikuroi in the leaves of chewing cane (Saccharum officinarum L.) - Sheng Lin; Yifei Zhou; Guanshui Chen; Yang Zhang; Yanyun Zhang; Wenjun Ning; Daren Pan (Sugar Tech, 2010)

Effects of market liberalization on income from sugarcane farming in Guangxi, China - Ze-Lin Qin (Sugar Tech, 2005)